The Influence of Service Quality on Customer Satisfaction Using the Banking Service Quality (BSQ) Method - Hidayat, Rahmad; Tosungku, La Ode Ahmad Safar; Pawitra, Theresia Amelia (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
This study aims to analyze service quality at Bank ‘X’ by applying the Banking Service Quality (BSQ) method. Service quality is a crucial factor in maintaining customer satisfaction and preserving the bank's competitiveness against other banks. The BSQ method is used to identify the dimensions of service quality that have the most influence on customer perceptions of services at Bank ’X’. This research employs a quantitative approach by collecting data through questionnaires distributed to customers of Bank ‘X’, the collected data are then analyzed using statistical techniques such as factor analysis to identify service quality variables that emerge from customer perceptions. Additionally, regression analysis is conducted to measure the influence of each dimension on customer satisfaction. The results of this research indicate a negative gap in the access variable, while the other variable experience a positive gap. Negative gap results are also found in the attributes of